Relationship of organic farming with halalan toyyiban - Mohamad, Noor Azian; Hasan, Quamrul (2017)
Everyone wants to consume safe and healthy foods. Also, the producers want to position their produce/product according to the market demands. However, our understandings on the terminologies describing and classifying the different production process are not clear and well documented.Therefore, the purpose of this research is to understand the popular terminologies-organic, and halalan toyyiban, and find out the relationship between them. We hypothesize that there might be some common characteristics between halalan toyyiban and organic farming.The findings might help both the consumers in selecting the produce/product and business people in promoting their products.In this, the method used is a qualitative research design.Sampling of data collection is used mainly by face-to-face interviewing of six persons involved at the farm and the secondary data as well. Research informants are farmers, volunteers, and student from the Sri Lovely Farm, a government-certified organic farm at Sik, Kedah.The research reveals new insights on the relationship of characteristics of organic farming with halalan toyyiban.The three commonly found characteristics are: 1) quality; 2) healthy; 3) natural/environmental friendly.Using the findings we are proposing a model on the relationship of organic farming with halalan toyyiban. This study is a first of this type and undertaken as an exploratory research; therefore, further study should be conducted to obtain more understanding and knowledge on this subject.